2024
DOI: 10.5534/wjmh.230034
|View full text |Cite
|
Sign up to set email alerts
|

Does Varicocele Repair Improve Conventional Semen Parameters? A Meta-Analytic Study of Before-After Data

Abstract: Purpose The purpose of this meta-analysis is to study the impact of varicocele repair in the largest cohort of infertile males with clinical varicocele by including all available studies, with no language restrictions, comparing intra-person conventional semen parameters before and after the repair of varicoceles. Materials and Methods The meta-analysis was performed according to PRISMA-P and MOOSE guidelines. A systematic search was performed in Scopus, PubMed, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 309 publications
0
1
0
Order By: Relevance
“…Patients with Kartegener syndrome have immotile cilia syndrome, due to abnormal morphology and function of the sperm tail ( 66 ). Varicocele, which is an important cause of male infertility, also results in an increased rate of abnormal sperm morphology ( 67 ). Some abnormalities that are related to varicocele include elongated sperm head and abnormal retention of cytoplasmic droplets ( 68 , 69 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Patients with Kartegener syndrome have immotile cilia syndrome, due to abnormal morphology and function of the sperm tail ( 66 ). Varicocele, which is an important cause of male infertility, also results in an increased rate of abnormal sperm morphology ( 67 ). Some abnormalities that are related to varicocele include elongated sperm head and abnormal retention of cytoplasmic droplets ( 68 , 69 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Fertility outcomes related to PeVD (with or without treatment) are not available for women. For men on the other hand, a large meta-analysis including 351 studies showed that conventional semen parameters improved significantly following varicocele repair in infertile patients [16].…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Correctable causes of male infertility can be treated with surgery, medications, and hormone therapy. Common conditions like varicocele and undescended testicles in children can be surgically treated to prevent or cure infertility [ 4 5 ]. For young men planning chemotherapy, storing sperm in a sperm bank in advance may be necessary.…”
mentioning
confidence: 99%